ESG uncertainty, investor attention and stock price crash risk in China: evidence from PVAR model analysis - Yu, Danni; Meng, Tiantian; Zheng, Minyu; Ma, Rongyi (Springer Nature, 2024)
ESG uncertainty refers to the discrepancies in ratings by multiple third-party ESG rating agencies, challenging investors in assessing a company’s true ESG status. This study integrates ESG rating data from six major Chinese agencies to construct an ESG Uncertainty Index. Using a PVAR model, it explores the bidirectional relationships among ESG uncertainty, investor attention, and stock price crash risk in the Chinese capital market. The findings reveal no direct causal relationship between ESG uncertainty and stock price crash risk. However, there is a bidirectional Granger causality between ESG uncertainty and investor attention, as well as between stock price crash risk and investor attention. This suggests that increased ESG uncertainty and stock price crash risk attract more investor attention, which in turn amplifies these issues. The study implies that investor attention mediates the relationship between ESG uncertainty and stock price crash risk, indirectly affecting the latter. These findings highlight the importance of enhancing information disclosure regarding ESG factors to improve market transparency and stability.